Conductive PEDOT:PSS coated polylactide (PLA) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) electrospun membranes: fabrication and characterization - Chang, Hui Chung (2016)
In the current study, electrospinning technique was used to fabricate composite membranes by blending of a synthetic polymer, polylactic acid (PLA) and a natural polymer, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), PHBV. Conductive membranes were prepared by dipping PLA/PHBV electrospun membranes into poly(3,4-ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS) solution, which is a biocompatible polymer. The coated and uncoated membranes were evaluated using several techniques. The electrical conductivity of the coated membranes was measured using a digital multimeter. In vitro cell cytotoxicity and cell viability were measured by culturing human skin fibroblast (HSF) cells onto the membranes using MTT assays. It was observed that electrospinning of 20% (w/v) PLA/PHBV with a weight ratio of 50:50 produced the most uniform fibers with no beads. It was observed that the wettability and surface roughness of the PEDOT:PSS coated PLA/PHBV membranes were greatly increased than uncoated membrane. The results of cell viability using MTT assay, cell attachment and cell proliferation showed that the conductive PEDOT:PSS coated PLA/PHBV membrane were more favorable for tissue engineering application than their uncoated counterparts.